Comprehensive treatment of patients with type 2 diabetes, complicated by diabetic kidney disease, with concomitant non-alcoholic steatohepatitis - Z.Ya. Kotsiubiichuk; А.А. Antoniv; O.V. Kaushanska; L.V. Kanovska; Yu.M. Yarinich (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. The purpose of research is to establish the effect of bicyclol on the clinical manifestations of non-alcoholic steatohepatitis (NASH), markers of liver damage in patients with non-alcoholic steatohepatitis, and diabetes mellitus type 2 (DM2), the degree of hepatocyte steatosis and the stage of liver fibrosis. Materials and methods. Studies were carried out in the dynamics of treatment in 60 patients with NASH with DM2 of moderate severity, of which 15 people (25.0 %) had DM2 in the compensatory stage, 45 (75.0 %) — subcompensated. Besides DM2, at the time of inclusion in the study patients with NASH had no other chronic somatic pathology in the active phase or in the stage of decompensation (heart, vascular, kidney, digestive system, blood and hematopoiesis, neurological, psychiatric, cancer, endocrine, rheumatic diseases, fatty liver disease of alcoholic origin), acute illnesses, pregnancy, lactation. Results. Bicyclol treatment was more effective than traditional therapy (essential phospholipids) due to reducing the severity of clinical syndromes of non-alcoholic steatohepatitis: astheno-vegetative, abdominal discomfort, dyspepsia, hepatomegaly (p < 0.05), as well as the activity of biochemical syndromes: cytolysis, cholestasis, mesenchymal inflammation (p < 0.05); it also decreased steatosis (p < 0.05), and contributed to the reversal of liver fibrosis (p < 0.05). In patients of both comparison groups, dyspepsia manifestations reduced significantly after treatment: nausea, belching, bloating disappeared. Thus, the number of patients with the symptoms of dyspepsia in group 1 decreased by 1.3 times after therapy (p > 0.05). Conclusions. Bicyclol treatment is more effective than traditional therapy for non-alcoholic steatohepatitis on the background of diabetes mellitus type 2 and may be recommended for use as first-line therapy for 3 months one or two times a year.